Back Cover: A Structurally Characterized Cobalt(I) σ‐Alkane Complex (Angew. Chem. Int. Ed. 15/2020). Issue 15 (26th February 2020) - Boyd, Timothy M.; Tegner, Bengt E.; Tizzard, Graham J.; Martínez‐Martínez, Antonio J.; Neale, Samuel E.; Hayward, Michael A.; Coles, Simon J.; Macgregor, Stuart A.; Weller, Andrew S.
Abstract : A cobalt norbornane σ ‐alkane complex was synthesized by a single‐crystal to single‐crystal solid/gas hydrogenation from a norbornadiene precursor, as described by S. A. Macgregor, A. S. Weller et al. in their Communication on page 6177 . The cover picture shows the title cobalt σ‐alkane complex within its anion cage, with the van der Waals surface highlighted. The non‐covalent interactions provided by the anion cage are essential for the stabilization of this remarkable complex.